The Axiological Aspect of Contemporary Narratives on Climate - Akram, Sara (Vilnius University Open Series, 2021)
The Polish prime minister’s narrative is based on economic context, which means that one of the most important values is economic development and safety. Responsibility is considered in relation to Polish citizens. Equality refers to dividing actions proportionally to responsibility of carbon dioxide’s emission. Particularly in this narrative appear implications of threatening Polish economy and Poland is viewed as a victim of inequality. The Christian ecologists’ narrative concentrates around climate equality. It is oriented with victims of climate crisis’s consequences who are the poorest and most vulnerable, being at the same time the least responsible for fossil fuels’ global emission. The more economically developed countries should take their responsibility for climate changes while Christians are also called to speak in the name of those who cannot. Thus another important value in this narrative is solidarity, necessary in both working out solutions and taking action. In each narrative appears a particular set of values connected with one another. Combined as a web, they correspond on both semantic and conceptual level.